Alternância de vogais médias posteriores em formas nominais de plural no português de Belo Horizonte - Katia Silva Tomaz (2006)
This research analyses the alternation between tonic posterior medium vowels, both opened [] and closed [o], in nominal forms of plural, in Brazilian Portuguese from Belo Horizonte: caroços ~ carços. There are three cases to be considered (Cf. MIRANDA, 2002). The first case includes names that present tonic posterior medium vowels opened in both forms singular and plural, such as cpo, cpos. The second one, on the contrary, includes names with tonic posterior medium vowels close in both forms singular and plural, such as sogro, sogros. However, the third case includes names that present tonics posterior mediumvowels closed in the singular and opened in the plural, such as coro, cros. Alves (1999), who studies the behavior of medium vowels [] and [o] in tonic position, points out that plural form is a strong conditioner to variation among such vowels. Based on this research, sound variation was analyzed in this experiment (opened or closed) of tonic posterior medium vowels in the plural number inflexion: miolos ~ milos. In order to analyze this alternation, we adopted, as theoretical base, multi-representative models: the Phonology of Use (BYBEE, 2001) and the Exemplar Theory (PIERREHUMBERT, 2001). Data was collected from 24 participants from Belo Horizonte as statistical analyses was performed with Minitab for Windows program, version 13. Non-structural factors such as age, gender, education and the individual were evaluated. Structural factors considered were token frequency and the lexical item. In this research token frequency factor was verified to be relevant in the case of alternation between the vowels [] and [o]. Also, the results corroborate the Phonology of Use proposal that less frequent words change first, in the case of sound change without phonetic conditioning (Cf. BYBEE, 2001; PHILIPS, 1984).